EFEKTIVITAS PERMAINAN SETATAK UNTUK PEMAHAMAN NUMERASI SISWA SEKOLAH DASAR - Gheia Inazh Dzaskyyah; Muhammad Fendrik; Guslinda (STKIP Subang, 2026)
This study aims to determine the effectiveness of the setatak game on elementary school students' understanding of numeracy. The research was motivated by the low numeracy skills of students influenced by conventional learning methods so that more interesting, active, and contextual learning innovations are needed. The setatak game was chosen because it is able to integrate playing activities with mathematics learning according to the characteristics of elementary school students. The study used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The study was conducted at SD Madani Islamic School Pekanbaru involving 23 students, consisting of 12 students of class III A as the experimental class and 11 students of class III B as the control class. The research instrument was a pretest and posttest to measure students' understanding of numeracy before and after the treatment. The results showed that the average pretest score of the experimental class increased from 62.08 to 90.00 in the posttest, while the control class increased from 59.09 to 80.00. The results of the normality test showed that the data were normally distributed and the homogeneity test showed that the data were homogeneous. Hypothesis testing using the Independent Samples t-Test yielded a significance value of 0.003 (<0.05), indicating a significant difference between the experimental and control classes. Furthermore, the N-Gain calculation showed that the experimental class obtained an average score of 0.7437 (high category), while the control class obtained an average score of 0.4782 (moderate category). Based on the research results, it can be concluded that the Setatak game is effective in improving elementary school students' numeracy understanding through more active, enjoyable, and contextual learning.